L'incapsulazione anaforica nell'italiano contemporaneo: analisi di un corpus giornalistico - Pecorari, Filippo (My University, 2016)
This paper proposes an empirical analysis of the forms and functions of anaphoric encapsulation in written Italian. The analysis is based on a corpus of 500.000 words, which includes texts taken from national newspapers, local newspapers and news reports. The main aim of the research is the discussion of previous hypotheses about typical morphosyntactic and informational features of encapsulation. The quantitative results of the investigation show that lexical encapsulators are realized more frequently by definite NPs than by demonstrative NPs; on the informational level, most encapsulators do not have the function of utterance topic usually assigned to them by the literature. The analysis also focuses on encapsulations with an enunciative or a logical relevance and highlights their relationship with journalistic discourse and its sub-genres.
Keywords: anaphora; anaphoric encapsulation; textual cohesion; journalistic language; empirical approach